Descemetectomy as therapy option for visually disturbing roll in Descemet's membrane - Cursiefen, C.; Bachmann, B. (Ophthalmologe, 2013)
The aim was to demonstrate the feasibility of targeted removal of a central visually disturbing roll in Descemet's membrane after complicated cataract surgery.Case report: a 76-year-old patient complained of halos and reduced visual acuity after external cataract surgery. At slit-lamp examination a central roll in Descemet's membrane was found (2 × 2 mm).A targeted central descemetectomy was performed by circular descemetorhexis around the defect. Early postoperative visual acuity improved and halos disappeared. At 2 months postoperatively best corrected visual acuity (BCVA) was 1.0 and the endothelial cell count was not significantly changed.Central targeted descemetorhexis is a safe therapeutic option for visually disturbing defects of Descemet's membrane.
EVALuna2:21125